The Complexity-based Explanatory Strategy, Biological Levels, and the Origin of Life - Slobodan Perović (Rivista di Estetica, 2018)
A long-standing debate on the causality of levels in biological explanations has divided philosophers into two camps. The reductionist camp insists on the causal primacy of lower, molecular levels, while the critics point out the inescapable shifting, reciprocity, and circularity of levels across biological explanations. We argue, however, that many explanations in biology do not exclusively draw their explanatory power from detailed insights into inter-level interactions; they predominantly require identifying the adequate levels of biological complexity to be explained. Moreover, the main explanatory strategies grounding both theoretical and experimental approaches to one of the central debates in contemporary biology, i.e., on the origin of life, are primarily and sometimes exclusively driven by issues concerning the levels of biochemical complexity, and these only subsequently frame more substantial and detailed accounts of inter-level biochemical interactions.